Mariel of Redwall / 4 - Jacques, Brian (The Redwall Chronicles, 2000)
The mousemaid Mariel achieves victory at sea for the animals of Redwall Abbey, fighting the savage pirate rat Gabool the Wild, warlord of rodent corsairs.